Impact of standardized clinical assessment and management plans on resource utilization and costs in children after the arterial switch operation. (28th June 2017) - Rathod, Rahul H.; Jurgen, Brittney; Hamershock, Rose A.; Friedman, Kevin G.; Marshall, Audrey C.; Samnaliev, Mihail; Graham, Dionne A.; Jenkins, Kathy; Lock, James E.; Powell, Andrew J.
Abstract: Background: Standardized Clinical Assessment and Management Plans (SCAMPs) are a quality improvement initiative designed to reduce unnecessary utilization, decrease practice variation, and improve patient outcomes. We created a novel methodology, the SCAMP managed episode of care (SMEOC), which encompasses multiple encounters to assess the impact of the arterial switch operation (ASO) SCAMP on total costs. Methods: All ASO SCAMP patients (dates March 2009 to July 2015) were compared to a control group of ASO patients (January 2001 to February 2009). Patients were divided into "younger" (<2 years) and "older" (2–18 years) subgroups. Utilization included all cardiology visits, tests, and procedures. Standardized costs were applied to each unit of utilization. Results: There were 100 historical and 63 SCAMP patients in the younger subgroup, and 163 historical and 165 SCAMP patients in the older subgroup. In the younger subgroup, the SCAMP had a 28% reduction in outpatient clinic visits ( P  < .001), a 52% reduction in chest radiographs ( P  < .001), a 21% reduction in electrocardiograms ( P  < .001), and a 30% total reduction in costs. In the older subgroup, the SCAMP had a 21% reduction in outpatient clinic visits ( P  < .001), a 20% reduction in chest radiographs ( P  = .05), a 10% reduction in echocardiograms ( P  = .05), a 25% reduction in exercise stress tests ( P  = .01), and a 14% total reduction in costs. The total cost savings of the ASO SCAMP was $216 649 in the first 6 years of the SCAMP. There was no difference in clinical outcomes between the historical and SCAMP cohorts. Conclusion: SCAMPs can improve resource utilization and reduce costs after the ASO operation while maintaining quality of care.